Financial Instability and Monetary Policy: The Swedish Evidence - U. Michael Bergman; Jan Hansen (Sveriges Riksbank, 2002)
This paper examines the relationship between financial instability and monetary policy within the Swedish economy. Based on a standard VAR model of monetary policy extended to include measures of financial instability and credit expansions, we examine the interaction between monetary policy and financial stability. We find that both higher interest rates, higher prices and lending expansions contribute to financial instability. As the effects from price shocks are strong and persistent compared to other shocks, our conclusion is that we cannot reject that price stability and financial stability are mutually consistent goals for monetary policy.
Keywords: C12; C22; 330; Financial instability; monetary policy; VAR model; structural shocks